Analisis Pemilihan Metode Quality Of Service Dengan Traffic Policing Dan Traffic Shaping Sebagai Pembanding Bandwidth Pada Cisco Router Internet Service Provider - Nofita Rismawati; Muhamad Femy Mulya (ULTIMA InfoSys, 2018)
Abstract— Bandwidth is a carrying capacity of data carriers on a network connection, using units of time in speed. The cost of bandwidth procurement is very expensive and if it is not set up with management and hardware support, good software or brainware will cause huge losses. Therefore, a quality service standard must be created in an Internet Service provider known as Quality of Service (QoS). On a Cisco Router there are several methods of Quality of Service configured in such a way that the bandwidth of an ISP can be restricted and well managed. Traffic Policing and Traffic Shaping are two methods of Quality of Service that are widely used and each has advantages and disadvantages in terms of technical and non technical. In this research will answer the use of the best Quality of Service method on Cisco ISP Router by using descriptive analysis through Quality of Service data analysis parameters. Index Terms— Bandwidth, Quality of Service